The relationship between trust, cognitive skills, and democracy: Evidence from 30 countries around the world - Daniel D. Schnitzlein (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2019)
Based on highly comparable data from the OECD PIAAC Programme, this note analyzes the relationship between generalized trust and cognitive skills among 30 countries around the world. The results show that the strength and direction of the relationship is not a universal characteristic but varies substantially among countries worldwide. A detailed descriptive analysis of this variation provides evidence that the relationship strengthens with the level of democracy in a country. In a second step, German separation and reunification is used as external variation in the level of democracy in the German PIAAC subsample. The results support the evidence from the cross-country analysis. Thus, the institutional framework in a country not only shapes an individual's level of trust but also amplifies the relationship between individual characteristics such as cognitive skills and generalized trust.
Keywords: P51; Z13; 330; Generalized trust; political institutions; cognitive skills; PIAAC